(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The mentality of methods of teaching mentally retarded students to read, phonematic hearing, skills of analysis and synthesis, visual perception, spatial perception did not develop well, creeping in the pronunciation of sounds. Incorrect pronunciation or absence of vowels is common, the lexical and grammatical sides of speech are not developed. In the development of connected speech, the ability to compose a sentence according to a situational picture, to convert nouns in a unit into plural nouns, to form a diminutive-caressing nouns of a horse, depending on the given andose, was also influenced by the way of games. The results of independent speech observation showed that when they compose a story with the help of a plot picture, it is of great importance to perform tasks such as telling what they saw, telling the text that was read for them, explaining.